The polyphonic hymns of Valentin Triller’s 'Ein Schlesich singebüchlein' (Wrocław 1555), ed. Antonio Chemotti, Warsaw 2019 - Marc Desmet (Muzyka, 2020)
Book review of: The polyphonic hymns of Valentin Triller’s 'Ein Schlesich singebüchlein' (Wrocław 1555), ed. Antonio Chemotti, Warsaw 2019